DETERMINATION OF QUERSETIN OBTAINED FROM ONION PEELS BY IR SPECTROSCOPY. - Ismayilova Sh.Y.; Iskenderov V.H.; Hajibayli T.A.; Aliyev H.Y.; Abdullayeva A.A. (Scientific Research and Experimental Development, 2024)
Quercetin is abundant in various vegetables and fruits such as apples, honey, raspberries, onions, red grapes, cherries, citrus fruits, and green and red leafy vegetables. This includes the high quercetin content in the yellow onion peel. Onions are one of the most important horticultural crops. In 2019, current production worldwide reached approximately 100 million tons, resulting in the generation of constant amounts of solid waste material. Current literature reports that the annual production of onion waste in Europe is about 500,000 tons, especially in large producing countries such as Spain, the Netherlands and the United Kingdom . Onion peels, the most common waste material from onion processing, represent a reservoir of molecules with valuable biofunctional properties. Within the (phyto)-complex, quercetin and its glycosylated forms play an important role in this context.